Successful Same-Day Discharge for Robot-Assisted Radical Prostatectomy: A Systematic Review and Meta-Analysis. Issue 4 (14th July 2022) - Uy, Michael; Millan, Braden; Jones, Conor; Sands, David; Matsumoto, Edward; Bay, Benjamin; Shayegan, Bobby
Abstract: Introduction: Same-day discharge (SDD) following robot-assisted radical prostatectomy (RARP) is emerging as the standard of care. We conducted a systematic review and meta-analysis to evaluate the differences in perioperative characteristics, complication/readmissions rates and satisfaction/cost data between inpatient (IP) RARP and SDD RARP. Methods: This study was conducted in accordance with the Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines and was prospectively registered with PROSPERO (CRD42021258848). A comprehensive search of PubMed®, Embase®, Cochrane Central Register of Controlled Trials, ClinicalTrials.gov and conference abstract publications was performed. A leave-one-out sensitivity analysis was performed to control for heterogeneity and risk of bias. Results: A total of 14 studies were included with a pooled population of 3, 795 patients, including 2, 348 (61.9%) IP RARPs and 1, 447 (38.1%) SDD RARPs. SDD pathways varied, though many commonalities were present in patient selection, perioperative recommendations and postoperative management. When compared to IP RARP, SDD RARP had no differences in ≥grade 3 Clavien–Dindo complications (RR: 0.4, 95% CI 0.2, 1.1, p=0.07), 90-day readmission rates (RR: 0.6, 95% CI 0.3, 1.1, p=0.10) or unscheduled emergency department visits (RR: 1.0, 95% CI 0.3, 3.1, p=0.97). Cost savings per patient ranged between $367 and $2, 109, and overall satisfaction was high at 87.5%–100%. Conclusions: SDD following RARP is both feasible and safe, while potentially offering health care cost savings with high patient satisfaction rates. Data from this study will inform the uptake and development of future SDD pathways in contemporary urological care such that it may be offered to a broader patient population.